Formation of fractal aggregates during green synthesis of silver nanoparticles - Singh M.; Sinha I.; Singh A.K.; Mandal R.K. (My University, 2025)
The aggregation behavior of silver nanoparticles (AgNPs) prepared by a green synthesis procedure using starch as the stabilizer was studied by the small angle X-ray scattering (SAXS) technique. The protecting ability of starch was affected by the presence of NaOH leading to different aggregation behaviors. In all the samples, mass as well as surface fractal regimes were observed. Assuming spherical form, the radii of nanoparticles were in the range of 11-17 nm. © 2010 Springer Science+Business Media B.V.